If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + b + 3b = 0 Combine like terms: b + 3b = 4b a + 4b = 0 Solving a + 4b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4b' to each side of the equation. a + 4b + -4b = 0 + -4b Combine like terms: 4b + -4b = 0 a + 0 = 0 + -4b a = 0 + -4b Remove the zero: a = -4b Simplifying a = -4b
| 1.33(18)= | | 1.33(17)= | | 1.33(16)= | | 3r+9(r-2)= | | f(x)=x^2-12 | | 1.33(14)= | | (3.141511263)(1234567890)= | | 2(z-7)=3z | | 1.33(13)= | | (-0.75)x+4=(-2) | | 1.33(12)= | | 5(n+7)+7=-9 | | 2a+b+3b= | | 1.33(11)= | | 6+(x+4)=5-(4x+7)+8 | | -6-6x=10-17 | | y=4x+27-6 | | 1.33(15)= | | 1+5x=8-2x | | .125(x+24)=.625x+9-.5x | | 21x-28xy= | | p^2=5+2p | | 1.33(20)= | | Y+0.06y= | | 1.33(21)=20 | | 42y+8=74 | | 1.33(21)= | | 2x+5-6x=8x-4-15 | | 1.33(22)= | | 0=x^2-x+2.49 | | 42y+8= | | 1.33(23)= |